Approaching the PIDE 'From Below': Petitions, Spontaneous Applications and Denunciation Letters to Salazar's Secret Police in 1964. (August 2021) - Simpson, Duncan
Abstract : Under the Salazar regime, many Portuguese citizens spontaneously interacted with the secret police (PIDE), sending it letters of denunciation, prospective applications and petitions. The historians of the Estado Novo, by reducing the nature of the relations between the PIDE and society to its mechanisms of top-down repression, have overlooked the significance of the phenomenon. Drawing on the inputs of the international bibliography on accusatory practices and 'everyday life' under dictatorship, this article looks at the PIDE through the subjective perspectives of the individual citizens who approached it 'from below', thereby nuancing and complementing the established narrative of violence and repression. It focuses on the instrumentalisation of the PIDE by ordinary citizens as: an influential sponsor; an appropriable device of coercion; an instrument of private conflict resolution; a platform for collaborative interaction with the regime; an economic opportunity. The article also puts forward an interpretation of these 'everyday' interactions as part of a broader system of governance used by the authorities of the New State.